2012
DOI: 10.2478/v10222-011-0040-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olive Oil with Low Calorie Diet on Blood Lipids in Hyperlipidemic Patients

Abstract: Key words: olive oil, low calorie diet, hyperlipidemia, serum lipids Serum lipid abnormality is a risk factor for cardiovascular disease. The aim of this research was to study the effect of olive oil with low--calorie diet on blood lipids in hyperlipidemic patients. The study was done on fi fty eight hyperlipidemic patients of both sexes and age range of 25-65 years. The patients received low-calorie diet based on 1400 kcal energy per day for 4 weeks, containing 32% fat, 18% protein and 50% carbohydrate. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These analyses revealed that CO ingestion does not significantly affect HC (WMD = −0.24 cm; 95% CI: −3.01, 2.54 cm, P = 0.867) (32,37,80), lean body mass (WMD = 0.01; 95% CI: −0.16, 0.19, P = 0.874) (31,33), or A:G ratio (WMD = −0.01; 95% CI: −0.03, 0.01, P = 0.271) (31,73).…”
Section: Hc Lean Body Mass and A:gmentioning
confidence: 99%
See 4 more Smart Citations
“…These analyses revealed that CO ingestion does not significantly affect HC (WMD = −0.24 cm; 95% CI: −3.01, 2.54 cm, P = 0.867) (32,37,80), lean body mass (WMD = 0.01; 95% CI: −0.16, 0.19, P = 0.874) (31,33), or A:G ratio (WMD = −0.01; 95% CI: −0.03, 0.01, P = 0.271) (31,73).…”
Section: Hc Lean Body Mass and A:gmentioning
confidence: 99%
“…Among 25 studies included in the systematic review, 8 were categorized as good quality (31,35,36,38,73,75,77,84), 6 were fair quality (45,32,47,79,82,83), and 11 were low quality (33,34,37,39,46,74,76,78,80,81,85). The details of the risk of bias in individual studies according to the domains used by the Cochrane Collaboration's tool are provided in Table 2.…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations